Pt encapsulated hollow mesoporous SiO2 sphere catalyst for sulfuric acid decomposition reaction in SI cycle. (22nd January 2019) - Khan, Hassnain Abbas; Iqbal, Muhammad Ibrahim; Jaleel, Ahsan; Abbas, Imran; Abbas, Syed Asad; Deog-Jung, Kwang
Abstract: Sulfuric acid (SA) decomposition is one of three key reactions in sulfur Iodine (SI) cycle to produce hydrogen. The catalysts for the decomposition should be active and stable in a wide temperature range of 550–900 °C. Pt based catalysts have been explored for the application, but suffered from the Pt loss in high temperature (∼850 °C). TiO2 and Al2 O3 are used as a support. They can stabilize Pt metal at higher temperature, but are degraded at the temperature lower than 700 °C. SiO2 supports with a high surface area are relatively stable in a sulfuric acid vapor stream, but the lower interaction with Pt results in high Pt sintering and Pt loss. Both Pt loss and Pt sintering at the high temperature are originated from Pt vaporization. Here, Pt metallic components are placed at the inner wall of hollow mesoporous SiO2 spheres (Pt-HMSS) to preserve Pt components even at 850 °C. PtOx vapor vaporized during the SA decomposition can be re-dispersed on the inner wall of mesoporous SiO2 shell, which can suppress the Pt loss; (1) temperature at outer wall is higher than temperature at inner wall during the endothermic reaction on Pt at the inner wall, (2) the mesoporous shell afford the long path to suppress the diffusion of PtOx vapor at the inner wall to the outer wall. Pt catalyst at the outer walls of hollow mesoporous SiO2 spheres (HMSS-Pt) is prepared and tested for clarifying the hypothesis. Additionally, TiO2 -Pt catalyst, one of highly stable catalytic systems for the SA decomposition, is also prepared and compared with the Pt-HMSS catalyst. Graphical abstract: Image 1 Highlights: Hollow SiO2 sphere supported Pt catalysts are prepared using polystyrene sphere. Stability of Pt at inner walls is much higher than that at outer wall. The Pt loss with Pt-HMSS is mainly due to the destruction of hollow shell. The severe Pt sintering is observed at the outer walls, but not at the inner wall. The encapsulation of Pt with SiO2 and TiO2 results in the high stability.